2018
DOI: 10.1002/cpch.46
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Prenylated Proteins Using Alkyne‐Modified Isoprenoid Analogues

Abstract: Protein prenylation involves the attachment of a farnesyl or geranylgeranyl group onto a cysteine residue located near the C-terminus of a protein, recognized via a specific prenylation motif, and results in the formation of a thioether bond. To identify putative prenylated proteins and investigate changes in their levels of expression, metabolic labeling and subsequent bioorthogonal labeling has become one of the methods of choice. In that strategy, synthetic analogues of biosynthetic precursors for post-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Consistent with previous findings, 35,38,39 statin treatment augmented isoprenoid analogue incorporation. Metabolic labeling in the brain with C15AlkOPP resulted in the identification of 17 prenylated proteins in the absence of statin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous findings, 35,38,39 statin treatment augmented isoprenoid analogue incorporation. Metabolic labeling in the brain with C15AlkOPP resulted in the identification of 17 prenylated proteins in the absence of statin.…”
Section: Discussionsupporting
confidence: 92%
“…In previous work, performed in cell culture, it has been demonstrated that treatment with a statin leads to increased incorporation of C15AlkOPP, as evidenced by a larger number of proteins identified with greater fold changes as well as by an increase in the identification of farnesylated proteins. 35,38,39 When WT mice were treated with C15AlkOPP in conjunction with simvastatin, a similar increase was seen with 37 prenylated proteins found, compared with 17 observed in the absence of statin. This 20protein increase included a significant increase in the number of FTase substrates.…”
Section: Prenylomic Profiling Of Brains From Wt Mice Following Icv In...mentioning
confidence: 62%
See 1 more Smart Citation
“…Multiple Small GTPases. To assess whether reducing the 607:558 ratio disrupts prenylation, we tested the incorporation of a synthetic isoprenoid probe, C15AlkOPP (29), after SSO treatment and conducted analysis by in-gel fluorescence and mass spectrometry (Fig. 4A).…”
Section: Sso Ex5 Inhibits the Prenylation And Downstream Signaling Ofmentioning
confidence: 99%
“…409 Furthermore, HeLa cells may not respond to isoprenoid labeling as efficiently as other cell lines do such as COS-7, which displayed excellent labeling with C15-Alk-OPP but not with C15-Alk-OH. 410 This disparity in labeling between cell lines using different forms of the isoprenoid probe can be rationalized with the observation that different cell-types respond with varying degrees of probe labeling with C15-Alk-OH. 411 Profiling of S-prenylated proteome in the macrophage cell line RAW264.7 yielded 23 Ca 1 a 2 X-containing and 12 Rab proteins using C15-Alk-OH.…”
Section: S-prenylated Proteome Profilingmentioning
confidence: 99%